Aeolian sediment reconstructions from the Scottish Outer Hebrides: Late Holocene storminess and the role of the North Atlantic Oscillation. (15th January 2016) - Orme, Lisa C.; Reinhardt, Liam; Jones, Richard T.; Charman, Dan J.; Barkwith, Andrew; Ellis, Michael A.
Abstract: Northern Europe can be strongly influenced by winter storms driven by the North Atlantic Oscillation (NAO), with a positive NAO index associated with greater storminess in northern Europe. However, palaeoclimate reconstructions have suggested that the NAO-storminess relationship observed during the instrumental period is not consistent with the relationship over the last millennium, especially during the Little Ice Age (LIA), when it has been suggested that enhanced storminess occurred during a phase of persistent negative NAO. To assess this relationship over a longer time period, a storminess reconstruction from an NAO-sensitive area (the Outer Hebrides) is compared with Late Holocene NAO reconstructions. The patterns of storminess are inferred from aeolian sand deposits within two ombrotrophic peat bogs, with multiple cores and two locations used to distinguish the storminess signal from intra-site variability and local factors. The results suggest storminess increased after 1000 cal yrs BP, with higher storminess during the Medieval Climate Anomaly (MCA) than the LIA, supporting the hypothesis that the NAO-storminess relationship was consistent with the instrumental period. However the shift from a predominantly negative to positive NAO at c.2000 cal yrs BP preceded the increased storminess by 1000 years. We suggest that the long-term trends in storminess were caused by insolation changes, while oceanic forcing may have influenced millennial variability. Highlights: We have reconstructed Late Holocene storminess in the Outer Hebrides. The records indicate increasing storminess trend peaking after 1000 cal yrs BP. Records from Hebrides and Norway suggest delayed response to positive NAO shift. Other regional records support abrupt increases coinciding with negative NAO periods. Indicates insolation and oceanic forcings on storminess in northern Europe.